If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + -2x = 7 Combine like terms: -3x + -2x = -5x -5x = 7 Solving -5x = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-5'. x = -1.4 Simplifying x = -1.4
| 2b+17=41 | | 32x^2-34+40=0 | | 18x-xy+7x=5x+20 | | -7(4+6k)=-4(9x-11)+9 | | 5cosX+6=4 | | 3y-5=0.5*4y+2 | | -5n+3(3+7n)= | | a(n)=n+0.6(n-1) | | (3+3)-3= | | -x-9=6x+5 | | a(21)=-1.4 | | (3+a)-3= | | 2.4=6f | | 8x=4x+48 | | 4x+2x=5x+x | | 4p-4=6p-4-2p | | 3x+4x+2x+x=360 | | 2.4=6.4 | | -x-9=-6x+5 | | Logx=0.55 | | .35x+8=21 | | 6x^2+3x+-180=0 | | 3+2.4x=1 | | 4x+4(x+7)=128 | | p=-5.4+-0.4q | | x+123456789=0 | | (6*n)+n=56 | | 5p+2q=-27 | | 2x+-6=6x+16 | | 10x+10=x-10 | | 8n^2-8n+5=0 | | 4p+2q=-28 |